Effects of Lipid Lowering Drugs on Arterial Stiffness: One More Way to Reduce Cardiovascular Risk? - Reklou, Andromachi; Katsiki, Niki; Karagiannis, Asterios; Athyros, Vasilios (Current Vascular Pharmacology, 2020)
Arterial stiffness (AS) is considered an independent predictor of cardiovascular disease (CVD) events. Among lipid lowering drugs, statins have a beneficial effect on AS, independent of their hypolipidaemic effect. Based on 3 meta-analyses and other studies, this effect is compound- and doserelated. Potent statins at high doses are more effective than less powerful statins. Ezetimibe (± statin) also seems to decrease AS in patients with dyslipidaemia. Fibrates have no effect on AS. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have data that beneficially affect all AS risk factors, suggesting a beneficial effect on artery compliance. However, there is no direct measurement of their effect on AS indices. In patients with dyslipidaemia, prescribing high dose statins (± ezetimibe) will not only decrease low-density lipoprotein cholesterol levels but also improve AS (in addition to other effects). This effect on AS may contribute to the observed reduction in vascular events.
Keywords: fibrate